2020
DOI: 10.1089/cyber.2019.0235
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Visual Parameters Between Normal Individuals and People with Low Vision in a Virtual Environment

Abstract: Patients with Low vision are known to experience difficulties in executing activities of daily living and visual search due to reduction in vision. There is a need to translate clinical parameters into a real world that is relevant so as to understand the patient's functional vision; this can be possible with virtual reality (VR). This prospective study included 53 normal and 30 low vision subjects older than 18 years of age in a tertiary care center. The low vision subjects were further classified into periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Two other studies evaluated the effect of visual field loss on functional vision using VR. 49 , 50 Gopalakrishnan et al, 49 for example, found that normal vision subjects performed better than low vision subjects in everyday tasks in a VR environment. They demonstrated that VR performance scores in patients with peripheral field loss (56.65) and central field loss (63.25) were lower ( P < 0.001) than normal vision subjects (87).…”
Section: Resultsmentioning
confidence: 99%
“…Two other studies evaluated the effect of visual field loss on functional vision using VR. 49 , 50 Gopalakrishnan et al, 49 for example, found that normal vision subjects performed better than low vision subjects in everyday tasks in a VR environment. They demonstrated that VR performance scores in patients with peripheral field loss (56.65) and central field loss (63.25) were lower ( P < 0.001) than normal vision subjects (87).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to sighted controls, low vision participants took twice as long to complete tasks in VR. People with peripheral vision loss took longer to complete tasks compared to people with central vision loss [36].…”
Section: Studyingmentioning
confidence: 90%
“…Studies that compared performance between sighted and low-vision participants can use VR headsets to make use of the high degree of experimental control and task flexibility that a virtual environment affords (e.g., [36]). While the previous simulation was tested via first-person perspective on a computer monitor, VR headsets allow for data collection in a fully simulated 3D environment.…”
Section: Studyingmentioning
confidence: 99%
“…An excel sheet with all the matrices mentioned above was generated for each subject at the end of the assessment. (Gopalakrishnan, 2020)…”
Section: Spatial Orientationmentioning
confidence: 99%